P118 How do foreign-born patients with tuberculosis access healthcare? a cohort analysis of referrals from general practice and the emergency department to a tertiary tuberculosis service. (15th November 2016) - Conway, S; Pitcher, A; Dart, S; Vaghela, D; Burman, MGK; Potter, J; White, VLC; Tiberi, S; Kunst, H
Abstract : Introduction: More than Seventy percent of active Tuberculosis (TB) cases in England are in patients born outside the United Kingdom (UK). Lack of access to primary healthcare is often cited as a barrier to TB control. We considered how patients with TB referred directly to outpatient services initially access healthcare. Method: A retrospective cohort analysis of all patients with active TB on the London TB register (LTBR) between April 2014 and April 2015 at a large urban tertiary referral centre. The route of referral to TB services was confirmed by a review of electronic patient records. We compared demographic, disease and outcome variables between groups as recorded in the LTBR. We excluded those requiring admission; identified through contact tracing; referrals from other secondary care outpatient services and those with inadequate data. Chi squared or Exact tests were used in the analysis. Results: We compared patients diagnosed with TB who were referred directly to outpatient services from General Practice (GP) (97 patients) and the Emergency Department (ED) (35 patients). There was no significant difference in age or sex between groups. Of those patients born outside the UK (105), 78 percent (82/105) were referred to clinic from their GP compared to only 56 percent (15/27) of those born within the UK (15/27). This difference was statistically significant (p < 0.05). There was no statistically significant difference between the mean length of stay in the UK amongst migrants that presented via ED or GP (MD 2.33 years, 95% CI: −2 to 7, p < 0.4). There was no statistically significant difference in the number of patients who had at least one social risk factor between groups. Comparing disease between the groups, there was a higher proportion of multisite disease amongst those referred from ED compared to GP (23% [8/35] vs 14% [14/97], p < 0.025), there was no statistical difference between the numbers of pulmonary cases identified or smear status between the groups. Conclusion: Amongst patients with active TB referred directly to outpatient services, those born outside the UK were more likely to have been referred by their GP than UK-born patients.